1986
DOI: 10.1172/jci112412
|View full text |Cite
|
Sign up to set email alerts
|

Ribose metabolism and nucleic acid synthesis in normal and glucose-6-phosphate dehydrogenase-deficient human erythrocytes infected with Plasmodium falciparum.

Abstract: The metabolism of pentose-phosphate was investigated in Plasmodium fakiparum-infected normal and glucose-6-phosphate dehydrogenase (G6PD)-deficient human red blood cells in vitro.5'-Phosphoribosyl-l-pyrophosphate (PRPP) content of infected normal red blood cells was increased 50-60-fold at the parasite trophozoite growth stage over that of uninfected cells. The PRPP increment in infected G6PD-deficient cells at comparable stage and parasitemia was only 40% of the value in normal infected cells. Red blood cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Parasite growth has been reported in some studies to be inhibited in RBC mutants with low GSH levels, such as in glucose‐6‐phosphate dehydrogenase (G6PD)‐deficient RBC [5–8], while in other studies parasite growth appeared to be normal in G6PD‐deficient RBC [5, 9]. Growth inhibition data [5, 9], and results by Roth et al [10]showing that GSH was extremely low in parasitized G6PD‐deficient RBC, seemed to imply that parasite GSH was dependent on the host's glutathione system.…”
Section: Introductionmentioning
confidence: 96%
“…Parasite growth has been reported in some studies to be inhibited in RBC mutants with low GSH levels, such as in glucose‐6‐phosphate dehydrogenase (G6PD)‐deficient RBC [5–8], while in other studies parasite growth appeared to be normal in G6PD‐deficient RBC [5, 9]. Growth inhibition data [5, 9], and results by Roth et al [10]showing that GSH was extremely low in parasitized G6PD‐deficient RBC, seemed to imply that parasite GSH was dependent on the host's glutathione system.…”
Section: Introductionmentioning
confidence: 96%
“…The reverse activity of the non-oxidative arm of PPP has also been demonstrated by measuring the incorporation of radiolabel from [1- 14 C]glucose into nucleotides [6,8]. The former investigators have shown that 4/5 of the glucose incorporated into parasite nucleic acids comes from the condensation of F6P and GAP in the reverse action of this arm.…”
Section: Introductionmentioning
confidence: 99%
“…Activity of 6-phosphogluconate dehydrogenase in Plasmodium- infected erythrocytes has been detected indirectly and alluded to a parasite enzyme, but not characterized [15-17]. Ribose-phosphate diphosphokinase of P. falciparum activity has been characterized and levels of its product 5'-phosphoribosyl-pyrophospate (PRPP) were measured in P. falciparum- infectederythrocytes [8,18]. The levels of PRPP were found to be increased 56-fold in infected cells at the trohozoite stage compared to uninfected erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, PRPP synthetase was shown to be strongly dependent on the level of reduced glutathione (GSH). Since G6PDH-deficient erythrocytes possess low GSH level, the activity of PRPP synthetase is low in these cells and restricts parasite growth rate (Roth et al, 1986).…”
Section: Wwwintechopencommentioning
confidence: 99%